Public Satisfaction With Public Services (Study At The Department Of Population nd Civil Registration Of Semarang City) - Harsoyo Harsoyo; Suparno Suparno (Institut Teknologi Sepuluh Nopember, 2021)
Public service is the role of the function of the state apparatus as a public servant, so that the position of the Government Apparatus in public services is very strategic because it determines the extent to which the government can provide the best possible service to the community and the extent to which the state carries out its role properly. The level of community satisfaction with public services at the Semarang City Population and Civil Registration Service is already good. This indicates that the community is satisfied with the performance that has been carried out by the government. In addition, every element of the Community Satisfaction Index assessment is all in the good category, although there are three elements that are of little value among others, namely service time, tariff, and product specifications for service types. The three types of public services are noted by the government to improve their performance in the future